FENOMENA GADAI LAHAN SAWAH DI KOTA PADANGSIDIMPUAN - Dalimunthe, Dermina (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Sometimes, individuals encounter financial difficulties in covering all their needs. In this regard, Islam advises its followers to extend a helping hand to those in need, manifested through acts such as grants and loans. Pawn agreements present an alternative solution for communities; however, the ironic reality is that pawn practices found in society often involve usury, which is prohibited by Islamic law. In the realm of Islamic commercial jurisprudence (Fiqh muamalah), a pawn agreement is referred to as